The effect of frequency of defoliation on the productivity of selected forage legumes (Stylosanthes hamata, Stylosanthes capitata and Centrosema pascuorum) in the sub-humid zone of Nigeria - Tarawali, G.; Mohamed-Saleem, M.A.; Chionuma, P.C. (Cambridge University Press, 1995)
The dry matter yield, nutritive value and persistence of three legume species (Stylosanthes hamata Taub., S. capitata Vog. and Centrosema pascuorum Mart. ex. Benth.) cut at different frequencies during the growing season or only once at the end of the growing season were compared. The shorter cutting intervals enhanced regrowth, but very frequent cutting reduced total dry matter and seed yields. A defoliation interval of three to six weeks is recommended. Generally, S.hamata gave the best performance.